Subduction initiation of the Neo-Tethys Ocean in Central Iran based on U-Pb geochronology, geochemical and Nd isotope data of the Ashin ophiolite - Shirdashtzadeh, Nargess; Furnes, Harald; Miller, Nathaniel R.; Dantas, Elton Luiz; Torabi, Ghodrat; Meisel, Thomas C. (Ofioliti, 2022)
Subduction initiation (SI) ophiolites are critical for reconstructing plate tectonic and magmatic evolution along ancient convergent margins. Here we integrate clinopyroxene and whole rock chemical compositions, whole rock Nd isotopic compositions, and zircon U-Pb geochronology to demonstrate that the Ashin ophiolite between the Torbat-e-Heydarieh-Sabzevar and Nain-Baft ophiolitic Belts, records the initiation of late Early Cretaceous subduction magmatism and formation of Neo-Tethys oceanic crust. Clinopyroxene and whole rock geochemical compositions of Ashin non-metamorphosed pillow lavas and ortho-amphibolites (metamorphosed pillow lavas) and ortho-amphibolitic dikes (metamorphosed diabase dikes) and whole rock compositions of comparable ophiolite exposures from Nain, Dehshir, and Shahr-Babak areas support a basaltic protolith generated during a subduction initiation system. Based on geochemical data, Sm/Nd > 0.4, Lu/Hf > 0.3, CeN/YbN < 1.2, DyN/YbN < 1.2, GdN/YbN < 1, LaN/YbN < 1, Th/Nb < 0.2 ratios, and εNdI > +9 can characterize the forearc basalt (FAB) affinity of ophiolitic mafic rocks. Geochronological (~ 107-94 Ma radiolarian cherts) and geochemical characteristics of the Ashin pillow lavas reflect a MORB-like forearc basin formed during subduction initiation towards the end of the Early Cretaceous. Then a younger group of basic pillow lavas and dikes formed and metamorphosed (to the amphibolites and amphibolitic dikes) in MORB-like (before 104 Ma) to SSZ-like (~ 97 Ma) SI settings based on zircon U-Pb ages and geochemical data. This short-lived oceanic basin (~ 13 Myrs, from ~ 107 to 94 Ma) closed at around 60 Ma (in Paleocene).